1980
DOI: 10.1063/1.91539
|View full text |Cite
|
Sign up to set email alerts
|

Ohmic contacts to p-type InP using Be-Au metallization

Abstract: A new contact to p-InP is reported with beryllium as the acceptor. The contact consists of a thin layer of 3 wt.% Be in Au alloy and a Au overlay sequentially deposited by e-gun evaporation. Alloying at 420 °C yields Ohmic contacts with low specific contact resistance rc⩽8×10−5 Ω cm2 for InP with NA−ND ≲1×1018 cm−3. To minimize the tendency of InP for thermal dissociation, the alloying temperature can be reduced to 375 °C by adding a thin Pd layer at the semiconductor metallization interface. This is achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Similar contacts using either Mn or Mg in place of Zn were not ohmic [63], but a Pd/Zn/Pd contact without the use of Ge was fabricated with contact resistivity in the mid 10-5 Q-cm2 [60]. Finally, contacts based on reducing the surface semiconductor bandgap using W-In-Sb to p-type InP with contact resistivity in the low 10-5 range were also reported [59].…”
Section: Contacts To Inpmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar contacts using either Mn or Mg in place of Zn were not ohmic [63], but a Pd/Zn/Pd contact without the use of Ge was fabricated with contact resistivity in the mid 10-5 Q-cm2 [60]. Finally, contacts based on reducing the surface semiconductor bandgap using W-In-Sb to p-type InP with contact resistivity in the low 10-5 range were also reported [59].…”
Section: Contacts To Inpmentioning
confidence: 99%
“…The conventional p-type ohmic contact to InP is AuZn based or AuBe based [60,61] although other p-type dopants have also been used with Au. Contact resistivity is dependent on the substrate doping and a typical value of 3.7 x 10-5 Qcm2 is achieved for doping level of 1018 cm-3 [60]. Alternative p-type contacts with better morphology have been reported using several approaches.…”
Section: Contacts To Inpmentioning
confidence: 99%
“…The contact metal usually contains a small amount of dopant. The contact metallizations reported for the InP/InGaAsP material system contain a small amount of dopant within an Au base (1,2,8).…”
Section: Methodsmentioning
confidence: 99%
“…After metallization, {he samples were alloyed in a forming gas atmosphere at 420~ The samples were placed in the furnace for 10 min, but approximately 4 min were required for the sample temperature to reach equilibrium. This same alloying procedure was applied to GaA1As and p-InP by Keramidas (3) and Temkin et al (2), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that the annealing temperature was reduced by about 20°C with the addition of Pd or Ni to AuZn contacts to p-InP, while the contact resistivity deteriorated. 10,23 However, the addition of Sb enabled the reduction of the annealing temperature of ϳ100°C in addition to greatly improving the contact resistivity. To the best of our knowledge, such a significant effect has not been reported previously.…”
Section: B Simultaneous Annealing For P-and N-inp Ohmic Contactsmentioning
confidence: 98%